Development of novel layer-by-layer assembled nanofiltration hollow fiber membranes for water treatment - Liu, Chang (2015)
Membrane technology has been studied extensively for water treatment over decades. The layer-by-layer (LBL) assembly method, which involves the build-up of polyelectrolyte multilayer (PEM) films on the surface or inside the pore structure of various membrane substrates, has shown great potential due to its extremely low thickness, highly controllable performance and simple procedures of formation. Therefore, this study aims to develop high performance hollow fiber membranes using the LBL assembly method for forward osmosis (FO) and water softening processes. In FO process, low concentration draw solution (less than 0.5M) was used to substantially reduce the draw solution (DS) replenishment, and the energy consumption for draw solution regeneration and separation. While in the water softening process, low operating pressure (less than 5bar) would be more suitable for hollow fiber membrane configuration with reduced energy consumption. With a solid understanding of the separation mechanisms of nanofiltration, a three-stage approach to develop the LBL assembled NF hollow fiber membrane has been adopted. At stage one, studies were conducted on the LBL deposition conditions to be applied on a polyethersulfone (PES) hollow fiber substrate. A simple deposition procedure by immersing the substrate into the polyanion poly(styrenesulfonic acid) (PSS) and polycation Poly(allylamine hydrochloride) (PAH) solutions alternately was used to achieve the desired number of deposition layers. With six layers of polyelectrolytes deposited, the membrane showed a high water flux of 40.5 l/m2 h with a low salt to water flux ratio, Js/Jv, of 0.201 g/L when using DI water as the feed and a 0.5 M MgCl2 solution as the draw solutions in the active layer facing draw solution (AL-facing-DS) orientation. In addition, 14.6 and 25.9 l/m2 h water fluxes with corresponding low Js/Jv ratios of 0.034 and 0.066 g/L can be achieved using 0.05 and 0.1 M draw solution concentrations, respectively, suggesting great potential of the LBL hollow fibers in the FO process. It is proved that the inner surface modification may possess several advantages over the shell side for the hollow fiber substrate such as better protection of selective layer, enhanced homogeneity and controllability of the chemical modification and reduced chemical requirement. Therefore in the following study, inner skin deposited LBL (id-LBL) membranes were fabricated using a semi-dynamic process in which the solutions were introduced /replaced in the fiber lumen by syringes followed by static contact for a desired time. The newly developed id-LBL membranes were then tested in NF and FO applications and the performance were compared with outer surface deposition as well as some literature data. It was found that the id-LBL membranes could not only withstand higher operating pressure but also possess superior hardness rejection especially in high concentration mixed salt solutions (more than 95% rejection to Mg2+ and Ca2+ in a 5000 ppm total dissolved salt (TDS) mixture under 4.8 bar). As for the FO process, of only two layer deposition, the id-LBL membranes also demonstrated significant performance improvement with increased water flux (up to 70 l/m2 h using 0.5 M MgCl2 as draw solution in AL-facing-DS configuration) and reduced salt leakage (around 0.5 g/m2 h using 1 M MgCl2 draw solution in AL-facing-FW configuration). It suggested that for hollow fiber substrate, the inner surface was also more suitable for the formation of the selective layer via LBL deposition than the outer surface. However, it was found later that the rejection of id-LBL membranes was drastically deteriorated in the presence of SO42- in the feed water due to the weakened charge effect while the size exclusion was expected to play a more important role. Therefore, glutaraldehyde (GA) crosslinking was adopted in combination with modified LBL deposition conditions to develop a novel hollow fiber NF membrane with low-pressure water softening capability for synthesized hard water containing divalent counter ion SO42-. Based on the membrane characterization results, the possible structure of the deposited layers and the effect of GA crosslink were proposed. It was found that the crosslinking could tighten the membrane surface pores with increased hydrophilicity while the membrane surface charge was reduced. The crosslinked LBL membrane showed more than 10 l/m2.h.bar permeability with above 95% rejection to each of 1,000 ppm MgCl2, MgSO4 and Na2SO4 solution under 2 bar pressure. It was also proven to be more suitable for the low-pressure water softening application at 2 bar in all tested feed water with the presence of SO42- and TDS up to 10,000 ppm in terms of both permeability and hardness removal efficiency when compared with commercial NF 270 and NF 90 membranes. The future plans for this project are proposed in three directions: (1) to scale up the crosslinked LBL membrane with the best water softening performance for pilot study and possible commercialization; and (2) to explore the further applications of LBL hollow fiber membranes by modifying membrane properties such as surface pore size and charge density based on current PES substrate.; (3) to develop microfiltration (MF) hollow fiber substrate suitable for LBL deposition and explore the possible applications.